2020
DOI: 10.1055/s-0040-1702164
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Anterior Cruciate Ligament Reconstruction with Hamstring Tendon Autografts: A Comparative Study of Three Different Techniques

Abstract: The ideal procedure for anterior cruciate ligament (ACL) reconstruction is one that can achieve anatomical restoration for a better ACL function. This retrospective comparative study was conducted to evaluate the objective and subjective clinical results of the conventional single-bundle femoral round (SBR) tunnel technique, the single-bundle femoral oval (SBO) tunnel technique, and the double-bundle (DB) surgical technique for anatomical ACL reconstruction with hamstring tendon autografts. Patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Mao et al 31 concluded that DB reconstruction provided better outcomes regarding anterior laxity and chrondroprotection with a minimum follow-up of 12 years. Similarly, Wen et al 53 found significant differences among groups on the results of the pivot-shift test at 1 and 2 years of follow-up. Kondo et al 54 divided subjective evaluation regarding pivot shift test in + and ++ in function of the examiner feeling when doing the test.…”
Section: Discussionmentioning
confidence: 82%
“…Mao et al 31 concluded that DB reconstruction provided better outcomes regarding anterior laxity and chrondroprotection with a minimum follow-up of 12 years. Similarly, Wen et al 53 found significant differences among groups on the results of the pivot-shift test at 1 and 2 years of follow-up. Kondo et al 54 divided subjective evaluation regarding pivot shift test in + and ++ in function of the examiner feeling when doing the test.…”
Section: Discussionmentioning
confidence: 82%
“…When preoperative and postoperative values were evaluated, Wen et al observed identical outcomes in the mean side to side difference. 12 Patients who underwent reconstruction using hamstring tendon autograft showed postoperative improvement in knee condition and a decrease in laxity at the end of 12 and 24 months. Over the course of two years, nearly all the study participants have recovered their normal knee function.…”
Section: Discussionmentioning
confidence: 89%
“…At the end of 12 and 24 months after surgery, patients who underwent reconstruction using a hamstring tendon autograft showed almost similar pattern of postoperative improvement in IKDC score. 12 The average side-to-side difference on the KT-2000 maximal manual force test for the Lachman test following surgery was 1.67±1.52 mm in a related study by Shahriar et al 13 The mean side to side difference value of We could only include a small number of cases because this was a time limited study, therefore the sample size was relatively smaller. The procedures were carried out by various surgeons at the same facility, which might have resulted in a small variance in method.…”
Section: Discussionmentioning
confidence: 92%